Избранное - Пушкин Александр Сергеевич (Библиотека мировой литературы для детей, 1994)
Экземпляры: КХ (19980327) / Инвентарный номер: 1021516 / Цена: / Сис.шифр: Р1 / Авт.знак: П 91 / ГРНТИ: 17.82 / ББК: 84(2=411.2)-4